Cold storage characteristics of hardy kiwifruit, Actinidia arguta ‘Autumn Sense’: comparison between two cold storage temperatures - Lee, Uk; Eo, Hyun Ji; Jung, Chung Ryul; Kim, Yonghyun (Frontiers in Plant Science, 2025)
Postharvest handling of hardy kiwifruit generally involves cold storage to prolong shelf life by delaying the ripening process. However, extended storage at near-freezing temperatures often results in undesirable chilling injury. To clarify the specific cold responses associated with the mitigation of chilling injury symptoms, we examined the physiological and molecular responses of hardy kiwifruit stored at very low (VL; 1°C) and moderate low (ML; 5°C) conditions. Fruits stored at VL conditions exhibited significantly delayed ripening. However, chilling injury symptoms such as pitting became increasingly severe during the mid to late phase of storage compared with that under ML conditions, indicating that VL conditions are more likely to induce chilling injury. Antioxidant activity in fruit stored under VL conditions was higher than that in fruit stored under ML conditions during the first four weeks, although the ascorbic acid content in VL-stored fruit steadily declined and remained lower than that in fruit stored under ML conditions. RNA-sequencing analysis revealed that most unigenes associated with antioxidant activity and the detoxification system were upregulated under VL conditions compared with that under ML conditions. Additionally, although unigenes involved in starch degradation were highly expressed under ML conditions, a subset of genes related to sucrose biosynthesis was upregulated under VL conditions, which corresponded to relatively higher sucrose levels in the later stages of storage. Our findings suggest that the antioxidant system and specific soluble carbohydrate metabolism are sensitive to lower cold storage temperatures, and their activation appears to contribute to the mitigation of chilling injury symptoms during storage.